A Descriptive analysis of British Accents in 'Bring Me The Horizon' Interview - Wiggy Ramadhani; Iwan Setiawan; Bibit Suhatmady (Universitas Muhammadiyah Enrekang, 2024)
The British accent, spoken by individuals from the United Kingdom (UK), comes in various forms.